E-268 Large vessel occlusion stroke transfers achieve faster arrival-to-puncture times and improved outcomes with direct-to-endovascular suite protocol. (23rd July 2022) - Regenhardt, R; Rosenthal, J; Dmytriw, A; Vranic, J; Bonkhoff, A; Bretzner, M; Hirsch, J; Rabinov, J; Stapleton, C; Patel, A; Singhal, A; Rost, N; et al.
Abstract : Introduction: For patients with large vessel occlusion (LVO) stroke, time to treatment with endovascular thrombectomy (EVT) is crucial to prevent infarction and improve outcomes. We sought to evaluate the arrival-to-puncture times and outcomes for transferred patients accepted directly to the angio-suite (LVO2OR) versus those accepted through the emergency department (ED) in a hub-and-spoke telestroke network. Methods: Consecutive patients transferred for EVT with spoke CTA-confirmed LVO, spoke ASPECTS >6, and LKW-to-hub arrival <6 hours were identified. Our LVO2OR protocol began implementation in January 2017. The LVO2OR cohort includes patients who underwent EVT from July 2017 to October 2020; the ED cohort includes those from January 2011 to December 2016. Arrival-to-puncture time and 90-day modified Rankin Scale (mRS) were prospectively recorded. Results: The LVO2OR cohort was comprised of 91 patients and the ED cohort 90. LVO2OR patients had more atrial fibrillation (AF, 51% vs 32%, p=0.02) and more M2 occlusions (27% vs 10%, p=0.01). LVO2OR patients had faster median hub arrival-to-puncture time (11 vs 92 minutes, p<0.001), faster median telestroke consult-to-puncture time (2.4 vs 3.6 hours, p<0.001), greater TICI 2b-3 reperfusion (92% vs 69%, p<0.001), and greater 90-day mRS <2 (35% vs 21%, p=0.04). In a multivariable model, LVO2OR significantly increased the odds of 90-day mRS <2 (aOR 2.77, 95%CI 1.07, 7.20; p=0.04) even when controlling for age, baseline mRS, AF, NIHSS, M2 location, and TICI 2b-3. Conclusion: In a hub-and-spoke telestroke network, accepting transferred patients directly to the angio-suite was associated with dramatically reduced arrival-to-puncture time and may lead to improved 90-day outcomes. Direct-to-angio-suite protocols should continue to be evaluated in other regions and telestroke models. Disclosures: R. Regenhardt: None. J. Rosenthal: None. A. Dmytriw: None. J. Vranic: None. A. Bonkhoff: None. M. Bretzner: None. J. Hirsch: None. J. Rabinov: None. C. Stapleton: None. A. Patel: None. A. Singhal: None. N. Rost: None. T. Leslie-mazwi: None. M. Etherton: None.